Thoracic scent efferent system of Pentatomoidea (Hemiptera: Heteroptera): a review of terminology - Kment, Petr; Vilímová, Jitka (Zootaxa, 2010)
The terminology used for structures constituing the thoracic scent efferent system is reviewed and discussed, with the emphasis on the Pentatomoidea. The most suitable terms are selected and suggested for a general use, i.e., scent gland system, metathoracic scent apparatus, thoracic scent efferent system, internal scent efferent system, internal orifice, vestibule, vestibular furrows, external scent efferent system, ostiolar plate, metepimeral pseudosuture, ostiole, ostiolar groove, periostiolar depression, vestibular scar, peritreme, supporting projection, median furrow, auricle, spout, (peritremal) groove, (peritremal) ruga, (peritremal) disc, peritremal lobes, terminal lobe, pseudoperitremal structures, pseudoperitreme, evaporatorium, evaporatory channel, gyrification, mycoid microsculpture, mycoid surface, mushroom body, stem, cap, bridge, alveole, trabeculae, peritremal microsculpture, peritremal surface. The traditional terminology describing the external scent efferent system (especially peritreme) in Cydnidae is discussed and reinterpreted. All the suggested terms are illustrated by scanning electron micrographs and an extensive synonymic list is given for most of them.